The study of groups - Klein, Josephine, 1926-2018. (London : Routledge, 1998)
In attempting to understand the psychological aspects of the developmental process and socialisation, the distinct disciplines of sociology and psychology were brought together for the first time. Titles in the Sociology of Behaviour and Psychology set of the International Library of Sociology analyse how behaviour is formed and learned.
1. The performance of tasks in groups -- 2. Differentiation in the groups : (1) : functional authority -- 3. Differentiation in the groups : (2) : status authority -- 4. The spread of information -- 5. The need for organisation -- 6. The evolution of norms -- 7. The evolution of likes and dislikes -- 8. Sentiment in the group : the impressive dimension -- 9. Communication as adaptive behaviour -- 10. Decision-making as instrumental behaviour : the dimension of control -- 11. The self-defeating process : latent pattern maintenance -- 12. The larger society and social change.
"First published in 1956 by Routledge and Kegan Paul, Ltd."
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Social groups; Sociology; Sociology; Sociologie; sociology; SOCIAL SCIENCE -- Anthropology -- General; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Sociology -- General; Social groups; Sociology